Shigley's mechanical engineering design - Budynas, Richard G.; Nisbett, J. Keith; Tangchaichit, Kiatfa (McGraw-Hill Education, 2021)
Shigley's Mechanical Engineering Design is intended for students beginning the study of mechanical engineering design. Students will find that the text inherently directs them into familiarity withboth the basics of design decisions and the standards of industrial components. It combines the straight forward focus on fundamentals that instructors have come to expect with a modern emphasis on design and new applications. This edition maintains the well-designed approach that has made this book the standard in machine design for nearly 50 years. McGraw Hill Education's Connect is also available as an optional add on item. Connect is the only integrated learning system that empowers students by continuously adapting to deliver precisely what they need when they need it how they need it so that class timeis more effective. Connect allows the professor to assign homework quizzes and tests easily and automatically grades and records the scores of the student's work. Problems are randomized to prevent sharing of answers an may also have a "multi-step solution" which helps move the students' learning along if they experience difficulty.